Self-regulated learning processes vary as a function of epistemic beliefs and contexts: Mixed method evidence from eye tracking and concurrent and retrospective reports. (April 2016) - Trevors, Gregory; Feyzi-Behnagh, Reza; Azevedo, Roger; Bouchet, François
Abstract: The objective of the current studies was to investigate how epistemic cognition related to specific phases and components of self-regulated learning and its adaptation to learning conditions of varying quality. In a multi-study, mixed method design, we presented university students with science content that relayed conceptual discrepancies and collected quantitative and qualitative data to study how students responded to discrepancies. In Study 1 ( n = 42), we collected eye tracking patterns, study times, and metacognitive ratings and found that participants adapted their behavioral processing as a function of their epistemic cognition and discrepancy type. In Study 2 ( n = 20), we collected concurrent think-aloud protocols and retrospective interviews to further explore why discrepancies were noticed (or not) and how they were resolved. Results revealed that prior knowledge and epistemic self-efficacy in oneself as an evaluator of knowledge emerged as important themes to detecting and efficiently resolving discrepancies. We conclude with a discussion of theoretical and methodological implications. Highlights: Interactions between epistemic cognition and self-regulated learning were examined. Discrepancies were presented to study resolution strategies. Eye tracking and metacognition correlated with epistemic cognition. Thematic analysis showed prior knowledge and self-efficacy were related to learning.